A New Report of Prawn, Macrobrachium altiforns (Henderson) From Singhia River Biratnagar, Nepal - Sharma, Anu; Subba, B.R. (Our Nature, 2006)
The prawn Macrobrachium altiforns of family Palaemonidae recorded from Singhia river Biratnagar, Nepal is described. Keywords: Prawn, Macrobrachium altiforns, Morphometry doi:10.3126/on.v2i1.322 Our Nature (2004) 2: 33-34